Electrosynthesis of Polythiophene/Cr2O3 Nanocomposite as a Model of Health Topics (Water Treatment) - Hanaa Kadtem Egzar (Journal of Global Pharma Technology, 2016)
A Nanocomposite film consisting of Cr2O3 and polythiophene (PT), has been successfully fabricated on a stainless steel substrate (SS) by a simply electrochemical deposition method. The fabrication mechanisms are based on electrolytic deposition ELD method of Cr2O3 thin film and electropolymerization deposition of PT. The papered Cr2O3 and PT/Cr2O3 were characterized by FT-IR, FESEM, TEM, XRD, and Raman spectra. Electrochemical degradation of Reactive Blue 4 (RB4) was studied by Cr2O3 and PT/Cr2O3 coated anodes in the existence of sodium chloride as a supporting electrolyte to investigate the effect of polythiophene /Cr2O3 Nano composite coating. The color removal efficiencies were 51.7% and 92 % respectively for above anodes, after 25 minutes of electrolysis at applied potential 3V.Keywords: Nanocomposite, Electrolytic deposition, Electrodegradation.